2017
DOI: 10.1364/optica.4.000323
|View full text |Cite
|
Sign up to set email alerts
|

Parity-time symmetry in coherently coupled vertical cavity laser arrays

Abstract: We report parity-time (PT) symmetry breaking in electrically injected, coherently coupled, vertical cavity surface emitting laser arrays. We predict beam steering, mode evolution and mode hopping as a consequence of the non-Hermiticity of the array analyzed by temporal coupled mode theory with both asymmetric gain distribution and local frequency detuning. We present experimental confirmation of the predicted mode evolution, mode hopping and PT symmetry breaking with quantitative agreement with the theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 63 publications
2
89
0
Order By: Relevance
“…In the past few years, a number of groups have demonstrated PT symmetry and its spontaneous symmetry breaking in optics by applying balanced gain and loss distributions, enabling novel optical elements such as perfect absorbers, invisibility, low power optical diodes, mode converter, and laser amplifiers . Very recently, PT symmetry has been imposed to microdisk and microring lasers . Ge and Stone have shown that thresholdless PT‐symmetry breaking can occur for certain modes in two‐dimensional and three‐dimensional geometries, which was found independently by Feng et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the past few years, a number of groups have demonstrated PT symmetry and its spontaneous symmetry breaking in optics by applying balanced gain and loss distributions, enabling novel optical elements such as perfect absorbers, invisibility, low power optical diodes, mode converter, and laser amplifiers . Very recently, PT symmetry has been imposed to microdisk and microring lasers . Ge and Stone have shown that thresholdless PT‐symmetry breaking can occur for certain modes in two‐dimensional and three‐dimensional geometries, which was found independently by Feng et al.…”
Section: Introductionmentioning
confidence: 97%
“…Recent developments in parity‐time (PT) symmetry have attracted considerable attention due to their potential applications in novel optical devices . PT symmetry was first proposed within the context of quantum physics as a framework to realize a real energy spectrum in a non‐Hermitian system .…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that for laser separation distances larger than those typically occurring in PICs or in cases where delays are intentionally introduced, such systems are described by delay-differential equations having a rich set of dynamical features [21][22][23][24].The introduction of topological characteristics in coupled lasers in terms of differential pumping and frequency detuning between the lasers [ Fig. 1(d)] enables the onchip implementation of a large set of key functionalities such as reconfigurable beam forming and steering [25], coherence tuning and enhanced phase-locking [26][27][28], localized syncrhonization [27,29], enhanced bandwidth and tailored modulation response [30,31] as well as existence of exceptional points allowing for ultra-sensitivity [32][33][34][35].In this work we consider the fundamental non-Hermitian optical meta-molecule consisting of two mutually coupled and differentially pumped semiconductor lasers as the basic reconfigurable oscillator element of a photonic integrated circuit exhibiting an extreme frequency tunability spanning over 100 GHz and controlled by minute changes of the electrically injected differential pumping. The latter is shown to control not only the frequency but also the shape of the underlying limit cycle providing a remarkable flexibility for the RF properties of the emited light beam.The time evolution of the electric fields and the number densities of two evanescently coupled diode lasers is governed by the following coupled single-mode rate equations for the amplitude of their normalized electric fields E 1 , E 2 , their phase difference θ and the normalized excess…”
mentioning
confidence: 99%
“…The introduction of topological characteristics in coupled lasers in terms of differential pumping and frequency detuning between the lasers [ Fig. 1(d)] enables the onchip implementation of a large set of key functionalities such as reconfigurable beam forming and steering [25], coherence tuning and enhanced phase-locking [26][27][28], localized syncrhonization [27,29], enhanced bandwidth and tailored modulation response [30,31] as well as existence of exceptional points allowing for ultra-sensitivity [32][33][34][35].…”
mentioning
confidence: 99%
“…A remedy to such an unwanted behavior is the introduction of gain/loss asymmetry which, as has been recently shown, not only enhances the stability of the system [29], but also admits controlled directed power transport enabled by the emergence of additional strongly asymmetric modes [30]. It is worth mentioning that the asymmetry as a stabilizer has been considered for other non-Hermitian photonic systems consisting of coupled lasers [31,32] but also for more general configurations of paired oscillators [33]. In addition, investigations on the key role of asymmetry on the formation and propagation of selflocalized beams in non-Hermitian configurations have shown that continuous families of solitary waves can be formed under generic conditions, not necessarily restricted by symmetry requirements [34]; as a result, they exhibit a rich set of propagation features such as dynamical trapping and controllable routing once the gain and loss spatial distribution is properly engineered [35,36].…”
Section: Introductionmentioning
confidence: 99%